Síntese de éteres derivados da 8-hidroxijulolidina via reação de Williamson - Santos, Carolina Rosa (2022)
Organic synthesis allows the use of different methodologies for modification or construction of new structures to later be applied in new purposes. Among so many approaches, the biological environment is more explored by these studies to find new ones that can be used efficiently in desired targets. N-heterocyclic compounds become interesting in this matter, since they have characteristics that allow their interaction with biological receptors, in addition to being like groups of biologically important molecules that already exist. Based on this, the research used a different molecule of Julolidine, which belongs to a class of Nheterocyclics, for the formation of increasing ethers linked to a different collection for further biological tests. A Williamson synthesis was performed, which consists of the formation of ethers by bimolecular nucleophilic substitution, using base and primary halides. As results, eight new compounds were obtained, with yields ranging from 34.93% to 68.44%, which were determined by 1H NMR, one of them by FT-ICR MS and two of them by X-Ray Crystallography. With the elucidation of the structures, it is possible to conclude that the Williamson reaction used was effective for the formation of desired derivates, being able to be a fast and more accessible option for the synthesis of new compounds, thus contributing to new research and the increase of julolidine ring’s molecules collection with different substituents, which can later be applied in several areas, such as biological ones.